Developing the Straddle-Sit Press to Handstand - Uzunov, V. (Gym Coach, 2012)
The straddle-sit press to handstand (SsPHS) is an extremely important early developmental skill in the training of young and developing gymnast. This article presents a systematic training approach to developing the SsPHS, it provides recommendations for the training of the three main areas: flexibility, strength, motor execution/performance. Based on the limited amount of empirical research examining the performance of this skill or its variations, several key points were extrapolated that could be of assistance to the coach when teaching this skill.